Internet of Things and Employee Engagement Across the Business Model in the Business Park Companies in Jordan - Al Shibly, Motteh S.; Albloush, Ahmad; Alkayid, Kholoud; Korany, Hossam; Alshurideh, Muhammad (International Review of Management and Marketing, 2024)
Businesses now function and engage with technology very differently as a result of the Internet of Things’ (IoT) rapid growth. This study investigates the connection between IoT adoption, the business models used by businesses located in a Jordanian business park, and its effect on employee engagement (EE). This research intends to offer insights into how the incorporation of IoT technology affects EE levels through the moderating role of business model’s mechanisms, in recognition of the critical role that engaged employees play in fostering organizational success. Data were gathered from 68 big companies a range of businesses inside a well-known commercial complex in Jordan using a quantitative approach, which also included questionnaires. Out 265 questionnaires were retrieved, 230 valid for analysis. PLS4 were employed to analyze the data. The results emphasize how closely intertwined IoT integration, components of business models, and employee engagement are. It has been discovered that the alignment of IoT- enabled processes with the business model’s strategies improves operational effectiveness, streamline workflows, and enhance EE. Limitation and future research are also provided.